The Practice of Imperialism and Colonialism in Development and Their Impact on the Community Economy: An Overview - Izzatun Naimah (Institut Agama Islam Negeri Jember, 2022)
This article describes the impact of development on the economy caused by the colonial government's practice of Imperialism and colonialism. Imperialism and colonialism assume that all wealth in a country belongs to the government. This practice has been going on for a long time since the Dutch colonial era, which is still felt today, even though Indonesia has become independent. These assumptions are eventually detrimental to society, especially in the economic aspect. In this case, the researcher wants to know how the effects of Imperialism and colonialism can affect the economy of the community, both in the past and in modern society today. In the results of this study, researchers found that there were still development policies in the colonial era that were still being implemented and significantly impacted society in general, especially in terms of the economy in Indonesia. The researcher used the descriptive qualitative method with a literature study. Researchers, in this case, will approach the economic and historical aspects more. This study only wants to see an overview of the impact of development on the economy that occurs in society.